Transformation des villes et mobilité durable : Regard sur les déterminants psychosociaux de l’attachement à l’auto solo - Anne-Sophie Gousse-Lessard; Jérôme Laviolette (VertigO)
In the context of the current socioecological crisis, mobility issues represent a staunch question. Quebec’s car-centric mobility system has well-documented negative consequences for the environment, health, quality of life, personal finances and for the province’s economy. In terms of climate, the road passenger transport sub-sector (cars and light trucks) alone is responsible for 22 % of Quebec's GHG emissions. Nevertheless, the rate of motorization is constantly progressing - the number of vehicles per adult in Quebec having increased by 30 % since 1990 – as well as the proportion of car trips. How can we explain and reverse these trends ? In Quebec, mobility has mainly been studied from the disciplines of transportation engineering and urban planning. The influence of structural (built environment, transport networks’ accessibility) and socio-demographic factors is therefore well understood. However, it seems that these approaches are not enough to understand the complexity of our car dependency and lead to the ambitious and radical transformations that the state of climatic emergency requires. Inspired by a growing body of research on the psychosocial aspects of mobility behaviors, a mixed-methods study combining citizen workshops and a questionnaire was designed to better understand the factors explaining car ownership and use. An exploratory segmentation approach has revealed three types of road users with very distinct psychographic profiles. The segments are presented as well as a reflection on the potential of change for each segment. Such a psychographic segmentation approach seems a relevant tool that, combined with structural considerations, could inform and guide public action towards more resilient cities